Dari Self-Love hingga Checkout: Wacana Feminis dan Logika Komodifikasi Influencer TikTok Profesional di Indonesia - Nuzzi Ulmi; Akhmad Fathur Fahlevi (Danudirja Setyabudi Nusantara, 2026)
This study examines how motivational content produced by a licensed psychologist–influencer on TikTok deploys feminist empowerment rhetoric as a mechanism of commercial commodification. Drawing on Sara Mills' feminist critical discourse analysis and Vincent Mosco's political economy of communication, we analyze five videos published by @Creator-P, an Indonesian content creator with over 800,000 followers, selected for their simultaneous deployment of psychological authority and commercial endorsement. Analysis reveals a consistent discursive pattern in which the creator occupies an expert subject position, constructing her female audience as bodies in need of commercial solutions, while positioning herself as both a peer and a promoter. Three interlocking commodification mechanisms are identified: content commodification, in which empowerment narratives are structured as advertising formats; audience commodification, in which parasocial intimacy is leveraged as consumer access; and what we term the credibility-commodity nexus, whereby professional authority is mobilized to naturalize consumption as self-improvement. These findings suggest that feminist discourse in Indonesian influencer culture functions not as a challenge to patriarchal consumption logics but as a legitimating vehicle for them. The study contributes an integrated discursive–economic framework applicable to the growing body of scholarship on postfeminist digital labor in Southeast Asian platform contexts.